Legal Assistance and Penal Mediation in Theft Cases Involving Physical Altercations: Enhancing Pancasila Values in Kenteng Village: Bantuan Hukum dan Mediasi Pidana dalam Kasus Pencurian dengan Kekerasan Fisik: Penanaman Nilai-Nilai Pancasila di Desa Kenteng - Arifin, Ridwan; Riyanto, R. Benny; Fibrianti, Nurul; Karsinah, Karsinah; Ananta, Bintang Rafli; Zainurohmah, Zainurohmah; Indraswara, Dede; Sulaksmi, Galih Niken Anggoto (Annual Review of Legal Studies, 2024)
Cases of theft leading to altercations pose significant legal and social challenges that require effective resolution strategies. In Kenteng Village, such incidents frequently escalate into prolonged conflicts between perpetrators and victims. This study aims to evaluate the effectiveness of legal assistance in theft cases through penal mediation, with a focus on reinforcing Pancasila values ​​at the village level. A qualitative approach with an in-depth case study methodology was employed. Data were collected through interviews with perpetrators, victims, authorities, and mediators, as well as document analysis. The study investigates how legal assistance and penal mediation can facilitate conflict resolution while supporting the application of Pancasila values ​​in the case resolution process. The findings reveal that integrated legal assistance and penal mediation can reduce tensions between disputing parties and increase the likelihood of peaceful resolution. Penal mediation, involving a third-party mediator, enables constructive dialogue and fair settlements, considering the interests of both parties. The reinforcement of Pancasila values, such as social justice, humanity, and unity, proves effective in fostering mutual respect and tolerance within the village community. In conclusion, legal assistance and penal mediation not only address legal disputes but also strengthen Pancasila values ​​within the community. Recommendations for future research include the development of mediation and legal assistance training programs based on Pancasila values ​​to extend their application to other regions.